2021
DOI: 10.1039/d1ra00401h
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur quantum dot-based “ON–OFF–ON” fluorescence platform for detection and bioimaging of Cr(vi) and ascorbic acid in complex environmental matrices and biological tissues

Abstract: A SQDs-based “ON–OFF–ON” platform is constructed for detection of Cr(vi) and AA. SQDs are feasible for bioimaging of zebrafish embryos/larvae and HeLa cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“… 35,36 The peaks observed at 3411 cm −1 and 1640 cm −1 are belonged to –OH and C O, respectively. 37 No other new IR peaks are observed from the synthesized SQDs, which indicates the physical interaction between the SQDs and PEG-400 instead of chemical interaction. The XPS and FT-IR characterization results above show that the surface of the synthesized SQDs is rich in hydrophilic groups, so the obtained SQDs have high water solubility and can be used as fluorescent probes in aqueous media.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“… 35,36 The peaks observed at 3411 cm −1 and 1640 cm −1 are belonged to –OH and C O, respectively. 37 No other new IR peaks are observed from the synthesized SQDs, which indicates the physical interaction between the SQDs and PEG-400 instead of chemical interaction. The XPS and FT-IR characterization results above show that the surface of the synthesized SQDs is rich in hydrophilic groups, so the obtained SQDs have high water solubility and can be used as fluorescent probes in aqueous media.…”
Section: Resultsmentioning
confidence: 95%
“…33,34 The peaks centered at 1113 cm À1 and 950 cm À1 could be attributed to the stretching vibration of C-O-H or C-O-C. 33 The peak at 2873 cm À1 in PEG-400 is split into two relatively sharper peaks at 2912 cm À1 and 2876 cm À1 , both of them are attributed to the stretching vibration of C-H. 35,36 The peaks observed at 3411 cm À1 and 1640 cm À1 are belonged to -OH and C]O, respectively. 37 No other new IR peaks are observed from the synthesized SQDs, which indicates the physical interaction between the SQDs and PEG-400 instead of chemical interaction. The XPS and FT-IR characterization results above show that the surface of the synthesized SQDs is rich in hydrophilic groups, so the obtained SQDs have high water solubility and can be used as uorescent probes in aqueous media.…”
Section: Characterization Of Sqdsmentioning
confidence: 95%
“…In addition to aqueous media, it was also found that SQDs can be utilized to detect Cr(VI) and AA in HeLa cells based on the fluorescence on–off–on phenomenon ( Figure 2E ). Wang’s group also used SQDs to detect Cr(VI) and AA in zebra fish embryos and larvae, and similar fluorescence on–off–on behavior was observed ( Xia et al, 2021 ).…”
Section: Biosensingmentioning
confidence: 83%
“…Copyright 2021, American Chemical Society. (C) Reproduced, with permission, from Xia et al (2021) . Copyright 2021, Royal Society of Chemistry.…”
Section: Cytotoxicity Evaluation and Bioimagingmentioning
confidence: 99%
See 1 more Smart Citation